Advances in Design - ElMaraghy, Hoda A.; ElMaraghy, Waguih H. (Springer Series in Advanced Manufacturing, 2006)
Advances in Design examines recent advances and innovations in product design paradigms, methods, tools and applications. It presents fifty-two selected papers which were presented at the 14th CIRP International Design Seminar held in May 2004 as well as the invited keynote papers. Dr. Waguih ElMaraghy was the conference Chair and Dr. Hoda ElMaraghy was on the program committee. The International Institution for Production Research (CIRP), founded in 1951, is the top production engineering research college worldwide. The CIRP is subdivided into Scientific and Technical Committees (STC's) which are responsible for coordinating cutting-edge research as well as holding highly regarded annual international seminars to disseminate the results. The CIRP "Design" STC meeting is the forum in which the latest developments in the design field are presented and discussed. The Springer Series in Advanced Manufacturing publishes the best teaching and reference material to support students, educators and practitioners in manufacturing technology and management. This international series includes advanced textbooks, research monographs, edited works and conference proceedings covering all subjects in advanced manufacturing. The series focuses on new topics of interest, new treatments of more traditional areas and coverage of the applications of information and communication technology (ICT) in manufacturing.